Advancing lipid nanoparticles: A pioneering technology in cosmetic and dermatological treatments - Pareek, Anil; Kapoor, Devesh U.; Yadav, Sandeep Kumar; Rashid, Summya; Fareed, Mohammad; Akhter, Mohammad Suhail; Muteeb, Ghazala; Gupta, Madan Mohan; Prajapati, Bhupendra G. (Colloid and interface science communications, 2025)
Lipid nanoparticles (LNPs) represent a groundbreaking advancement in the realms of cosmetics and dermatology, providing advantages over traditional formulations. This paper explores the revolutionary potential of LNPs, particularly Solid Lipid Nanoparticles (SLNs) and Nanostructured Lipid Carriers (NLCs), in enhancing cosmetic and dermatological applications. The review highlights the advantages of LNPs, including improved skin penetration, improved bioavailability and controlled release of active ingredients, which together contribute to their superior performance compared to conventional formulations. Notable applications discussed include their roles in acne treatment, anti-aging solutions, wound healing, skin-lightening products, and sunscreens. This study examines the structural features and formulation techniques of LNPs, highlighting biocompatibility, and targeted delivery capabilities. We also explore emerging uses such as genetic medicine and mRNA vaccine delivery, alongside market trends and consumer acceptance. By summarizing recent developments and identifying existing challenges, this paper offers a thorough overview of LNPs for future research in pharmaceutical and cosmetic advancements. [Display omitted] •Lipid nanoparticles penetrate the skin through transcellular, intercellular and follicular penetration.•LNPs showed escalated skin penetration, enhanced bioavailability with controlled release profiles.•LNPs are useful in treating infectious as well as inflammatory skin disease.•LNPs showed significant effect in cosmeceuticals such as anti-aging, Skin brightening, Sunscreen.